Facile electrospinning formation of carbon-confined metal oxide cube-in-tube nanostructures for stable lithium storage. Issue 59 (11th July 2017) - Liu, Ziang; Guo, Ruiting; Meng, Jiashen; Liu, Xiong; Wang, Xuanpeng; Li, Qi; Mai, Liqiang
Abstract : A smart design of cube-in-tube nanostructures was realized by a facile precursor-modified electrospinning method with subsequent pyrolysis, which exhibit excellent electrochemical performance in lithium batteries. Abstract : A unique carbon-confined metal oxide cube-in-tube nanostructure is synthesized by a facile precursor-modified electrospinning method with subsequent pyrolysis. This nanostructure has a partly graphitized carbon layer with manganese oxide nanoparticles embedded as the tube and amorphous CoSnO3 hollow cubes uniformly distributed inside the tube. As a lithium-ion battery anode, this architecture exhibits a high reversible discharge capacity and rate capability.